2003
DOI: 10.1083/jcb.200212114
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of cell motility and invasion by FAK

Abstract: Cell migration and invasion are fundamental components of tumor cell metastasis. Increased focal adhesion kinase (FAK) expression and tyrosine phosphorylation are connected with elevated tumorigenesis. Null mutation of FAK results in embryonic lethality, and FAK−/− fibroblasts exhibit cell migration defects in culture. Here we show that viral Src (v-Src) transformation of FAK−/− cells promotes integrin-stimulated motility equal to stable FAK reexpression. However, FAK−/− v-Src cells were not invasive, and FAK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
431
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 490 publications
(467 citation statements)
references
References 59 publications
24
431
2
3
Order By: Relevance
“…As treatment of control 4T1 cells with inhibitors to Src-family PTKs, JNK and MEK1-ERK blocked uPA expression, and previous studies have shown that FAK can promote Src, JNK and ERK activation , it is possible that a multi-protein signaling complex with FAK generates signals to ERK and JNK leading to changes in uPA expression. This conclusion is supported by the fact that v-Src-stimulated cell invasion is linked to the formation of a FAK-Src-p130Cas-Dock180 signaling complex, elevated Rac and JNK activation and increased MMP expression and activity (Hsia et al, 2003). Further, inhibition of Src and MAPK activation blocks an ErbB2/3 to FAK signaling linkage, promoting cell invasion (Benlimame et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…As treatment of control 4T1 cells with inhibitors to Src-family PTKs, JNK and MEK1-ERK blocked uPA expression, and previous studies have shown that FAK can promote Src, JNK and ERK activation , it is possible that a multi-protein signaling complex with FAK generates signals to ERK and JNK leading to changes in uPA expression. This conclusion is supported by the fact that v-Src-stimulated cell invasion is linked to the formation of a FAK-Src-p130Cas-Dock180 signaling complex, elevated Rac and JNK activation and increased MMP expression and activity (Hsia et al, 2003). Further, inhibition of Src and MAPK activation blocks an ErbB2/3 to FAK signaling linkage, promoting cell invasion (Benlimame et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…As FAK facilitates invadopodia formation by v-Src (Hauck et al, 2001;Hsia et al, 2003), we investigated the localization and activity of FAK within murine 4T1 breast carcinoma cells (Figure 1). 4T1 cells are highly invasive and spontaneously metastasize upon orthotopic implantation in BALB/c mice (Aslakson and Miller, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations